Sennoside A inhibits quorum sensing system to attenuate its regulated virulence and pathogenicity via targeting LasR in Pseudomonas aeruginosa - Han, Xiaofeng; Nan, Mengyue; Cai, Xinyu; Qiao, Boling; Chen, Lin; Shen, Lixin (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is an important opportunistic pathogen, and the emergence of drug resistance greatly increased the difficulty of treating its infection. Cell density-dependent quorum sensing (QS) system not only regulates the virulence but also associates with the drug resistance of P. aeruginosa. Screening for agents targeting QS to inhibit bacterial virulence and pathogenicity is considered a promising strategy to combat P. aeruginosa infection. In the present study, sennoside A was found to be able to inhibit the QS expression of P. aeruginosa at subinhibitory concentrations. The QS-regulated virulence factors, including protease, elastase, rhamnolipid, and pyocyanin, were also inhibited by sennoside A at both transcriptional and translational levels. Moreover, sennoside A could suppress the motility of twitching, swimming, and swarming as well as the biofilm formation, which is associated with the acute and chronic infections of P. aeruginosa in a dose-dependent manner. The attenuated pathogenicity of P. aeruginosa by sennoside A was further verified by Chinese cabbage, Drosophila melanogaster, and Caenorhabditis elegans infection analysis. Further study found that sennoside A might target the las system, mainly LasR, to interfere with QS. All the results indicate that sennoside A could inhibit the QS system to attenuate its regulated virulence and pathogenicity via mainly targeting LasR in P. aeruginosa and further research to identify its anti-QS activity for other Gram-negative bacteria is warranted.